Ischemia and No Obstructive Coronary Artery Disease: Prevalence and Correlates of Coronary Vasomotion Disorders. (December 2019) - Ford, Thomas J.; Yii, Eric; Sidik, Novalia; Good, Richard; Rocchiccioli, Paul; McEntegart, Margaret; Watkins, Stuart; Eteiba, Hany; Shaukat, Aadil; Lindsay, Mitchell; Robertson, Keith; Hood, Stuart; et al.
Abstract : Background: Determine the prevalence and correlates of microvascular and vasospastic angina in patients with symptoms and signs of ischemia but no obstructive coronary artery disease (INOCA). Methods: Three hundred ninety-one patients with angina were enrolled at 2 regional centers over 12 months from November 2016 (NCT03193294). INOCA subjects (n=185; 47%) had more limiting dyspnea (New York Heart Association classification III/IV 54% versus 37%; odds ratio [OR], 2.0 [1.3–3.0]; P =0.001) and were more likely to be female (68% INOCA versus 38% in coronary artery disease; OR, 1.9 [1.5 to 2.5]; P <0.001) but with lower cardiovascular risk scores (ASSIGN score median 20% versus 24%; P =0.003). INOCA subjects had similar burden of angina (Seattle Angina Questionnaire) but reduced quality of life compared with coronary artery disease; subjects (EQ5D-5 L index 0.60 versus 0.65 units; P =0.041). Results: An interventional diagnostic procedure with reference invasive tests including coronary flow reserve, microvascular resistance, and vasomotor responses to intracoronary acetylcholine (vasospasm provocation) was performed in 151 INOCA subjects. Overall, 78 (52%) had isolated microvascular angina, 25 (17%) had isolated vasospastic angina, 31 (20%) had both, and 17 (11%) had noncardiac chest pain. Regression analysis showed inducible ischemia on treadmill testing (OR, 7.5 [95% CI, 1.7–33.0]; P =0.008) and typical angina (OR, 2.7 [1.1–6.6]; P =0.032) were independently associated with microvascular angina. Female sex tended to associate with a diagnosis of microvascular angina although this was not significant (OR, 2.7 [0.9–7.9]; P =0.063). Vasospastic angina was associated with smoking (OR, 9.5 [2.8–32.7]; P <0.001) and age (OR, 1.1 per year, [1.0–1.2]; P =0.032]. Conclusions: Over three quarters of patients with INOCA have identifiable disorders of coronary vasomotion including microvascular and vasospastic angina. These patients have comparable angina burden but reduced quality of life compared to patients with obstructive coronary artery disease. Microvascular angina and vasospastic angina are distinct disorders that may coexist but differ in associated clinical characteristics, symptoms, and angina severity. Clinical Trial Registration: URL: https://www.clinicaltrials.gov . Unique identifier: NCT03193294. Abstract : Supplemental Digital Content is available in the text.